Simulation of pollutants from excess use of urea fertilizer - E Jabbar Al_Defiery, Mahammed (Al-Qadisiyah Journal of Pure Science, 2018)
The pollution problem occupies a private importance in the world because of health and environmental risks and events changes will ultimately lead to the destruction of life and the imbalance on this earth. Therefore, the aim of this study is the modeling simulation of pollutants resulting from the excessive use of urea fertilizer on food and environment. However, due to many effects including the health problems caused by the containment of water and food by nitrate, ozone layer depleted, air pollution with ammonia and nitrogen oxides, emergence of the phenomenon of eutrophication in rivers and water basins and the occurrence of soil deteriorating. Two experiments conducted on two soils from different sites in the Hilla city to study ammonium volatilities and leached nitrate by adding two different levels of urea 150 and 250 kg N ha within incubated at 3, 6 and 9 days. The results showed that most of the loss was from urea added to soils in the first 6 days of incubation and increased loss by increasing fertilizer application. The soil 1 and soil 2 recorded concentrations of ammonia volatilities accumulated 86 and 73 mg kg soil during 9 days of incubation at the second level of fertilizer, while the highest concentrations of nitrate 66 and 69 mg kg at leached water from soil 1 and soil 2 respectively within first 3 days of incubation. The study also showed that there are two types of pollutants were caused from urea fertilizer; the first polluter is CO2, which is up 46.6% of the total weight of urea fertilizer (T). The second polluter is contaminated nitrogen represents the total quantities of volatile ammonia (M), nitrogen oxides liberation (N), nitrate transmitted to the water (W) and nitrates accumulated in the food (F). The model of simulations for the total amount of pollutants resulting from the urea (S) outcome from urea is: S = 0.466 T + K (M+N+W+F)